Determinants of sales profitability for Polish agricultural distributors - Piotr Korneta (International Journal of Management and Economics, 2019)
Due to volatile micro- and macroeconomic conditions and increasing competition, companies experience great difficulties in attaining required profitability. The objective of this paper is to identify the profitability determinants for Polish agricultural distributors in a recent period, i.e., 2006-2016. The potential determinants of profitability identified during the course of literature review and after interviews with industry experts are classified into internal and external. With the use of Spearman correlation ranks and regression analysis of figures relating to 24 Polish agricultural distributors, the following internal profitability determinants are identified: age, size, working capital components, indebtedness, salaries, and sales margins. Additionally, the study confirmed the influence of the following selected external profitability determinants: market share, unemployment rate, and several industry-specific variables. This paper proposes the first set of sales profitability determinants for Polish agricultural distributors. The results of this study are interesting for industry-level management.
Keywords: M10; M41; A12; Q17; L11; L21; 650; profitability; sales; return on sales (ROS); distribution; agriculture